Pengobatan Alternatif Bekam Kering terhadap Kadar Kolesterol Darah - Syokumawena Syokumawena; Marta Pastari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the effectiveness of dry cupping alternative treatment on blood cholesterol levels. The research method in this study used a pre-experimental design with a two-group pre-and post-test design. The results showed that most of the blood cholesterol levels before cupping were nine people (30.0%) with worrying blood cholesterol levels (200-239). Most of the blood cholesterol levels before 13-point cupping were 11 people (36.7%) with High Blood Cholesterol Levels (>240), then after 13-point cupping, 11 people (36.7%) had Worrying Blood Cholesterol Levels (200-239). In conclusion, groups 9 and 13 cupping points affect reducing blood cholesterol levels. Keywords: Cupping, Cholesterol, Alternative Medicine